YWHAE silencing induces cell proliferation, invasion and migration through the up-regulation of CDC25B and MYC in gastric cancer cells: new insights about YWHAE role in the tumor development and metastasis process - Leal, Mariana Ferreira (Oncotarget, 2016)
We previously observed reduced YWHAE (14-3-3ε) protein expression in a small set of gastric cancer samples. YWHAE may act as a negative regulator of the cyclin CDC25B, which is a transcriptional target of MYC oncogene. The understanding of YWHAE role and its targets is important for the better knowledge of gastric carcinogenesis. Thus, we aimed to evaluate the relationship among YWHAE, CDC25B, and MYC in vitro and in vivo. For this, we analyzed the YWHAE, CDC25B, and MYC expression in YWHA-silenced, CDC25B-silenced, and MYC-silenced gastric cancer cell lines, as well as in gastric cancer and non-neoplastic gastric samples. In gastric cancer cell lines, YWHAE was able to inhibit the cell proliferation, invasion and migration through the reduction of MYC and CDC25B expression. Conversely, MYC induced the cell proliferation, invasion and migration through the induction of CDC25B and the reduction of YWHAE. Most of the tumors presented reduced YWHAE and increased CDC25B expression, which seems to be important for tumor development. Increased MYC expression was a common finding in gastric cancer and has a role in poor prognosis. In the tumor initiation, the opposite role of YWHAE and CDC25B in gastric carcinogenesis seems to be independent of MYC expression. However, the inversely correlation between YWHAE and MYC expression seems to be important for gastric cancer cells invasion and migration. The interaction between YWHAE and MYC and the activation of the pathways related to this interaction play a role in the metastasis process.